Biosynthetic Microcin J25 Exerts Strong Antibacterial, Anti-Inflammatory Activities, Low Cytotoxicity Without Increasing Drug-Resistance to Bacteria Target - Yu, Haitao; Shang, Lijun; Yang, Guangxin; Dai, Ziqi; Zeng, Xiangfang; Qiao, Shiyan (Frontiers in Immunology, 2022)
Multidrug resistant (MDR) bacterial infection has emerged, raising concerns about untreatable infections, and posing the highest health risks. Antimicrobial peptides (AMPs) are thought to be the best remedy for this problem. Here, we showed microcin J25 (MccJ25) exhibited excellent bactericidal activity against standard and clinically relevant veterinary MDR strains with high stability, no cytotoxicity, and no increase in drug resistance. Analysis of antimicrobial mechanism possessed by sensitive enterotoxigenic Escherichia coli (ETEC) based on electron microscopy and Sytox Green methods was carried out. Results showed excellent activity against ETEC was due to permeabilizing bacterial membranes and strong affinity. MccJ25 exhibited high endotoxin-neutralizing activity in both in vivo and in vitro environments, and mice exposed to lipopolysaccharide (LPS) showed decreased plasma LPS levels and improved survival after administration of MccJ25. In an LPS-treated mouse septicemia model, MccJ25 treatment significantly alleviated inflammatory responses by inhibiting proinflammatory factor secretion and expression. In a mouse E. coli infection model, administration of MccJ25 effectively improved host defense against clinically source cocktail of multidrug-resistant E. coli strains induced intestinal inflammation and bacteria dissemination. Results of studies on anti-inflammatory mechanisms showed that MccJ25 downregulated nuclear factor kappa B kinase and mitogen-activated protein kinase, thereby reducing the production of toll-like receptor 4, myeloid differentiation factor 88 and decreasing the key proinflammatory cytokines. These findings clarify MccJ25 may be an ideal antibacterial/antiendotoxic drug candidate that has the potential to further guide the development of anti-inflammatory and/or antimicrobial agents in the war against MDR bacterial infection.